ANALISIS TATA KELOLA KELEMBAGAAN DALAM PENGELOLAAN PERHUTANAN SOSIAL DI KABUPATEN TORAJA UTARA: Analysis Of Institutional Governance In Social Forestry Management In North Toraja Regency - BIMANTARA, TEGUH; Andi Khairil A. Samsu (Program Studi Kehutanan Universitas Muslim Maros, 2025)
Social Forestry (PS) is a forest management program that grants management rights to local communities to access and manage forest areas legally and sustainably. This program not only aims to preserve the forest, but also to improve the welfare of the community, including in the aspect of food security and self-sufficiency.This study aims to evaluate the management of Community Forest (HKm) in North Toraja Regency with a focus on institutional and business aspects. Data collection was conducted through observation, structured interviews, and examination of institutional documents in three Forest Farmer Groups (KTH), namely Tambuntana, Tombang Riri, and Sipaelle. The sampling technique used purposive sampling and quota sampling methods. The results showed that the planning and institutional aspects were in the good category, with average scores of 110 and 109.57 respectively. However, other obligations such as the preparation of annual reports were classified as poor with a score of 39.13, indicating a lack of attention to documentation of activities. Community empowerment scored moderately well (46.09), which was influenced by the suboptimal role of Forest Management Unit extension workers in training and marketing Non-Timber Forest Products. The business governance aspect was also categorized as quite good (87.61), supported by the existence of a group business structure, but constrained by a lack of training and market access. Supporting factors for HKm management include the existence of planning documents, the desire to preserve the forest, and assistance from the government. Meanwhile, inhibiting factors include the lack of member involvement, limited human resources, and not optimal government support in marketing Non-Timber Forest Products. Overall, the performance of community forest management in the three forest farmer groups is in the good category, but needs improvement in the aspects of administrative obligations and community empowerment.